Aircraft structures for engineering students - Megson, T. H. G. (Thomas Henry Gordon) (Elsevier aerospace engineering series., 2013)
Aircraft Structures for Engineering Students is the leading self contained aircraft structures course text. It covers all fundamental subjects, including elasticity, structural analysis, airworthiness and aeroelasticity. Now in its fifth edition, the author has revised and updated the text throughout and added new examples and exercises using Matlab(c). Additional worked examples make the text even more accessible by showing application of concepts to airframe structures. Includes a Solutions Manual available to all adopting teachers. * New worked examples throughout the text aid understanding and relate concepts to real world applications * Matlab examples and exercises added throughout to support use of computational tools in analysis and design * An extensive aircraft design project case study shows the application of the major techniques in the book * More end of chapter exercises, with an accompanying Solutions Manual (for instructors only) at http://textbooks.elsevier.com.